Structure and evolution of metapolycentromeres - E. O. Grishko; P. M. Borodin (Вавиловский журнал генетики и селекции)
Metapolycentromeres consist of multiple sequential domains of centromeric chromatin associated with a centromere-specific variant of histone H3 (CENP-A), functioning collectively as a single centromere. To date, they have been revealed in nine flowering plant, five insect and six vertebrate species. In this paper, we focus on their structure and possible mechanisms of emergence and evolution. The metapolycentromeres may vary in the number of centromeric domains and in their genetic content and epigenetic modifications. However, these variations do not seem to affect their function. The emergence of metapolycentromeres has been attributed to multiple Robertsonian translocations and segmental duplications. Conditions of genomic instability, such as interspecific hybridization and malignant neoplasms, are suggested as triggers for the de novo emergence of metapolycentromeres. Addressing the “centromere paradox” – the rapid evolution of centromeric DNA and proteins despite their conserved cellular function – we explore the centromere drive hypothesis as a plausible explanation for the dynamic evolution of centromeres in general, and in particular the emergence of metapolycentromeres and holocentromeres. Apparently, metapolycentromeres are more common across different species than it was believed until recently. Indeed, a systematic review of the available cytogenetic publications allowed us to identify 27 candidate species with metapolycentromeres. Тhe list of the already established and newly revealed candidate species thus spans 27 species of flowering plants and eight species of gymnosperm plants, five species of insects, and seven species of vertebrates. This indicates an erratic phylogenetic distribution of the species with metapolycentromeres and may suggest an independent emergence of the metapolycentromeres in the course of evolution. However, the current catalog of species with identified and likely metapolycentromeres remains too short to draw reliable conclusions about their evolution, particularly in the absence of knowledge about related species without metapolycentromeres for comparative analysis. More studies are necessary to shed light on the mechanisms of metapolycentromere formation and evolution.